PENINGKATAN KETERAMPILAN BERBICARA BAHASA INGGRIS MELALUI METODE GAMES - S. Sumihatul Ummah MS (Research Institute and Community Engagement of IAIN MADURA, 2011)
In English subject in university, lecturer often finds the difficulty to learn college students to be able to converse English truly and fluent to tell the opinion or enquiring. This research tries to solve those problems the through the class action at semester college students II Tadris English STAIN Pamekasan passing game method. Having taken thrice rotations ( 3 cycles) activity with completion in each rotations, this research proves that game can improve the bravery and college students skill at English conversing subject ( Speaking English ). College student performance at I cycle is sentence structure (structure) with score 82,5%, while at uppermost II cycle is utterance clarity (comprehensibility) equal to 85% and uppermost III cycle is fluency (fluency) and pronunciation equal to 85% and 95%. Beside that, college student performance percentage also obtained in each cycles progressively, such as those are described at percentage I cycleI equal to 55,31% with category enough; II cycle equal to 65% with category enough and at III cycle equal to 70% with good category. Thereby is suggested that curator lecturer of conversing English subject can apply games method in overcoming the problem of ability to communicate in English, by creating interesting study atmosphere, pleasing, dynamic, creative, and pleasing